Fabrication of super capacitor and perovskite-sensitized solar cell for the assembly of photo-super capacitor - Ng, Chi Huey (2018)
The coupling of a solar cell with a super capacitor is gaining interest owing to its superior photo-to-electrical conversion efficiency and its in-situ energy storage ability for green and sustainable energy development. In this work, the electrochemical performances of the fabricated super capacitor and perovskite solar cell were individually measured for the fabrication of a photo-super capacitor. A Bi2O3/MnO2 based symmetrical and asymmetrical super capacitor were fabricated. The symmetrical super capacitor could charge up to 1.0 V, which gave a specific capacitance of 136.4 F/g at a scan rate of 2 mV/s. The power and energy densities of the bismuth-based symmetrical super capacitor were 51.8 W/kg and 7.1 Wh/kg, respectively and were improved to 25.6 Wh/kg and 115.3 W/kg when a Bi2O3/MnO2 positive electrode was integrated to a polypyrrole/reduced graphene oxide (PyR) negative electrode. It thus proven the feasibility of an asymmetrical super capacitor to promote the performance of a super capacitor. The dissatisfying stability performance of the Bi2O3/MnO2//PyR asymmetrical super capacitor (60% capacitance retained) prompted for screening of other pseudocapacitive materials. An asymmetrical super capacitor comprising a positive cobalt oxide/zinc oxide/reduced graphene oxide electrode (RZCo) and a negative polypyrrole/reduced graphene oxide electrode was then fabricated. A wide operational potential range for the RZCo//PyR asymmetrical super capacitor resulted in a high specific capacitance of 470.8 F/g, as opposed to the Bi2O3/MnO2 symmetrical super capacitor of 136.4 F/g and 144.1 F/g for the bismuth-based asymmetrical super capacitor, at a scan rate of 2mV/s, additionally exhibited 1.6-fold higher in energy and power densities, which fulfilling the criteria as the energy storage device for the photo-super capacitor.Perovskite solar cells were fabricated from a series of cesium based halide mixtures perovskite harvesting materials, denoted as CsPbBr3-xIx, where x = 0-0.3. An optimum iodide concentration of CsPbBr2.9I0.1 perovskite solar cell with an efficiency of 3.9% was fabricated. The solar cell achieved an open circuit voltage of more than 1.0 V and a fill factor of 64% by employing Spiro-OMeTAD as a hole transporting material with enhanced stability. The performances of the CsPbBr2.9I0.1 solar cell with P3HT/MoO3 hole transporting material was also investigated. The deeper HOMO and shallower LUMO level of the hole and electron transporting materials, respectively has achieved high Voc of 1.23 V, but with lower power conversion efficiency of 2.51% due to reduction in the Jsc, implies an additional charge loss processes at the interface of perovskite/HTM. In high humidity of more than 80 percent, the perovskite solar cell comprising CsPbBr2.9I0.1 achieved an efficiency of 0.46%. The perovskite solar cell retains 70% of its original efficiency after a week storage in dark and 33% efficiency retained under UV and air exposure at a high relative humidity of more than 80% for 24 hours. The integration of the perovskite solar cell and the asymmetrical super capacitor enabled simultaneous photoconversion and charge storage within the photo-super capacitor. The photovoltage and photocurrent measurements were successfully performed, evidencing that the photo-super capacitor was responsive to light illumination. Referred to the photovoltage measurement, zero voltage was presented at the first 50 s without the shine of light. Subsequently, the photovoltage was abruptly shooted up to ~80 mV and continue increasing to 90 mV for 100 s in the presence of light, and was then decreases drastically when light was switched off. To further proof the energy conversion and storage of the photo-super capacitor, the photocharged integrated device was galvanostatically discharged in dark at the current of 0.1 mA. As the integrated device reaches the cut off potential of 0.07 V, the discharging process took place in dark with the connection of only super capacitor’s electrodes, thus shows the workability of the photo-super capacitor. To enable practical application, improvizations such as optimizing thickness of each active layer and encapsulation of the photo-super capacitor are needed to prevent electrolyte loss.